Analisis Sifat Mekanis Baja ST60 Setelah Mengalami Pack Carburizing Karbon Variasi Temperatur 700⁰, 800⁰, 850⁰, 900⁰ - Pramuka Ilmu Purboputro (Creative Research in Engineering (CERIE), 2025)
Solid carburization can increase the hardness and wear resistance of steel compared to other methods. In this study, carburizing was carried out using temperatures of 700⁰, 800⁰, 850⁰, 900⁰. With this number of variations, the researcher will analyze the physical properties and mechanical properties of ST60 steel after undergoing carbon pack carburizing. In the Rockwell hardness test, the ASTM E 140-02 standard is used. In the Rockwell hardness test results, the hardness value of the raw material before pack carburizing increased after the material was carburized. Thus, the temperature in the carburizing process affects the hardness of the material. Then in the results of the raw material microstructure test, there are more ferrite crystals than pearlite. While the microstructure in pack carburizing has more pearlite crystals than ferrite. This shows that the steel workpiece has increased hardness after undergoing the carburizing process.